Risk Stratification for Bipolar Disorder Using Polygenic Risk Scores Among Young High-Risk Adults - Biere, Silvia; Kranz, Thorsten M.; Matura, Silke; Petrova, Kristiyana; Streit, Fabian; Chiocchetti, Andreas G.; Grimm, Oliver; Brum, Murielle; Brunkhorst-Kanaan, Natalie; Oertel, Viola; Malyshau, Aliaksandr; Pfennig, Andrea; et al. (Frontiers in Psychiatry, 2020)
Objective: Identifying high-risk groups with an increased genetic liability for bipolar disorder (BD) will provide insights into the etiology of BD and contribute to early detection of BD. We used the BD polygenic risk score (PRS) derived from BD genome-wide association studies (GWAS) to explore how such genetic risk manifests in young, high-risk adults. We postulated BD-PRS would be associated with risk factors for BD. Methods: A final sample of 185 young, high-risk German adults (aged 18–35 years) were grouped into three risk groups and compared to a healthy control group (n = 1,100). The risk groups comprised 117 cases with attention deficit hyperactivity disorder (ADHD), 45 with major depressive disorder (MDD) and 23 help-seeking adults with early recognition symptoms (ER: positive family history for BD, (sub)threshold affective symptomatology and/or mood swings, sleeping disorder). BD-PRS was computed for each participant. Logistic regression models (controlling for sex, age, and the first 5 ancestry principal components) were used to assess associations of BD-PRS and the high-risk phenotypes. Results: We observed an association between BD-PRS and combined risk group status (OR = 1.48, p < .001), ADHD diagnosis (OR = 1.32, p = .009), MDD diagnosis (OR = 1.96, p < .001) and ER group status (OR = 1.7, p = .025; not significant after correction for multiple testing) compared to healthy controls. Conclusions: In the present study, increased genetic risk for BD was a significant predictor for MDD and ADHD status, but not for ER. These findings support an underlying shared risk for both MDD and BD as well as ADHD and BD. Improving our understanding of the underlying genetic architecture of these phenotypes may aid in early identification and risk stratification.